Hubungan Pengetahuan Dengan Perilaku Pemeriksaan IVA (Inspeksi Visual Dengan Asam Asetat) Pada Wanita Usia Subur di Wilayah Kerja Puskesmas Kowel - Berliana Ayuning Asmara (Pusat riset dan Inovasi Nasional, 2025)
Cervical cancer is a deadly disease and ranks as the fourth most common cancer among women, according to the World Health Organization. In Indonesia, it is the second most prevalent cancer affecting women. Visual Inspection with Acetic Acid (VIA) is an early screening method to detect cervical cancer, yet its coverage remains low in several areas of East Java. This study aims to examine the relationship between knowledge and VIA screening behavior among women of reproductive age in the working area of Kowel Public Health Center. The study employed an analytical observational design with a cross-sectional approach. A total of 70 respondents were selected using accidental sampling. Data were collected through questionnaires assessing both knowledge and VIA screening behavior. Data analysis was conducted using the chi-square test. The results showed that 38 respondents had good knowledge, while 32 had poor knowledge. The chi-square test yielded a p-value of 0.494 (p > 0.05) and a prevalence ratio (PR) of 1.684. These results indicate no significant relationship between knowledge and VIA screening behavior. However, respondents with good knowledge were 1.684 times more likely to undergo VIA screening than those with poor knowledge. It is recommended that the Kowel Health Center enhance its educational efforts through more engaging and creative counseling methods using media tools such as brochures, leaflets, posters, and animated videos, delivered both directly and via social media, to attract public interest.